Theme and rheme analysis on viral dialogue of the series "Queen Charlotte: A Bridgerton Story" - Waluyo Waluyo; Herni Mayang Sari; Anggie Isma Aprianti; Linda Astuti Rangkuti; Meida Rabia Sihite (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This research aims at analyzing theme and rheme of the viral dialogue of the series Queen Charlotte: A Bridgerton Story and evaluating the success of the viral dialogue of the series Queen Charlotte: A Bridgerton Story. This study was conducted because the dialogue went viral and many people are impressed by the meaning of the dialogue. This study was conducted by employing qualitative approach. The data of this research were the viral dialogue of the series Queen Charlotte: A Bridgerton Story episode 6. The data were collected by using observation. The data were analyzed by comparing, describing, classifying and displaying by using table and description. The results showed that there were 5 Unmarked Simple Theme (55,5%), 3 Unmarked Multiple Theme (33,3%), no Marked Simple Theme found in the dialogue and 1 Marked Multiple Theme (11,1%). Based on the data, it is textually found the text is dominated with UST (Unmarked Simple Theme). The reason for this theme to be dominant was the function of “markedness” which is to give special status within the clauses. Contextually, the dialogue is about a romantic relationship between Queen Charlotte and a guy named George. The guy expresses his true feelings towards Charlotte and his desire to love her for life. The field of the text is romantic love or a romantic relationship. The dialogue has successfully conveyed the message by the mode of primarily declarative and expressive.